2017
DOI: 10.1080/13880209.2016.1277767
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis, antiproliferative and antioxidant activities of Chrozophora tinctoria : a natural dye plant

Abstract: Context:Chrozophora tinctoria (L.) A. Juss. (Euphorbiaceae) is known as ‘dyer’s-croton’ and used to obtain dye substances. Recently, natural antioxidants and colorants have been of interest because of their safety and therapeutic effects.Objective: This study investigates the antiproliferative and antioxidant activities of the various extracts and fractions from C. tinctoria and analyzes their phytochemical contents.Materials and methods: The aerial parts of C. tinctoria were extracted with water, ethyl acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
2
14
1
Order By: Relevance
“…The results of this study indicated that TPCs of the C. tinctoria accessions varied significantly from 26.01 (mg GAEg −1 DW) in C.t (2) to 10.9 (mg GAEg −1 DW) in C.t (8) (Table ). These findings are consistent with those of Oke‐Altuntas et al (), who have reported that TPC of C. tinctoria ranged between 9.17 ± 0.64 (µg GAE mg −1 ) and 186.37 ± 1.10 (µg GAE mg −1 ). Shahwar, Shafiq ur Rehman, Naeem, Sami, and Muhammad () have determined that TPC of ethyl acetate extract of C. tinctoria was 353.5 ± 5.5 (mg GAE g −1 ) of crude leave extract.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The results of this study indicated that TPCs of the C. tinctoria accessions varied significantly from 26.01 (mg GAEg −1 DW) in C.t (2) to 10.9 (mg GAEg −1 DW) in C.t (8) (Table ). These findings are consistent with those of Oke‐Altuntas et al (), who have reported that TPC of C. tinctoria ranged between 9.17 ± 0.64 (µg GAE mg −1 ) and 186.37 ± 1.10 (µg GAE mg −1 ). Shahwar, Shafiq ur Rehman, Naeem, Sami, and Muhammad () have determined that TPC of ethyl acetate extract of C. tinctoria was 353.5 ± 5.5 (mg GAE g −1 ) of crude leave extract.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, the results of their later study indicated a noticeable radical scavenging effect in the leaf methanol extract of C. tinctoria (IP% = 26.4 ± 0.2 µg/ml). Among the main phenolics in C. tinctoria , gallic acid exhibited the highest antiproliferative and radical scavenging abilities (IC 50 < 5 µg/ml) (Oke‐Altuntas et al, ). Furthermore, the leaf extracts obtained using different extraction methods exhibited higher radical scavenging activity than the reference compound BHT (Butylated hydroxytoluene) (Oke‐Altuntas et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations